2022
DOI: 10.1039/d2cp00477a
|View full text |Cite
|
Sign up to set email alerts
|

Excluded volume interactions and phase stability in mixtures of hard spheres and hard rods

Abstract: In this paper we study excluded volume interactions, the free volume fraction available, and the phase behaviour, in mixtures of hard spheres (HS) and hard rods, modeled as spherocylinders. We...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…First we evaluated the accuracy of our method for hard spherocylinders for various values of γ. In a previous study, 54 we already confirmed the accuracy of eq 5a for a specific aspect ratio of γ = 6. In Figure 3a, the data points are Monte Carlo computer simulation results for the free volume fraction, and the curves are predictions of eq 5b.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…First we evaluated the accuracy of our method for hard spherocylinders for various values of γ. In a previous study, 54 we already confirmed the accuracy of eq 5a for a specific aspect ratio of γ = 6. In Figure 3a, the data points are Monte Carlo computer simulation results for the free volume fraction, and the curves are predictions of eq 5b.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In section 3 of the Supporting Information, it is shown that eq is the canonical equivalent to the expression used for the semi-grand canonical potential of a colloidal mixture in FVT. ,, This method has recently been used to study phase boundaries in binary mixtures of hard spheres and hard rod/sphere mixtures. , In these works, ordered phases of only one component were accounted for whereas the depletants are treated as a fluid with a constant chemical potential that is fixed by an external reservoir. Because we are interested in mapping the phase behavior of colloidal mixtures in which both particles can form ordered phases, a canonical ensemble, without the need to use an external reservoir, is used here.…”
mentioning
confidence: 99%
“…Here, we present a simple and general framework that enables one to compute the phase behavior of colloidal mixtures, including anisotropic particles, and we apply this to the case of rods (spherocylinders) mixed with spheres and also show results for binary mixtures of platelets (disks) and rods. The phase behavior of binary mixtures of colloidal particles has been investigated previously with a variety of theoretical methods such as density functional theory (DFT), , Parsons–Lee theory (PL), , and free volume theory (FVT). ,, However, these studies include positionally ordered phases of only one component. This imposes a limitation on the range of applicability with regard to size ratios and concentrations and does not allow computation of the coexistence between a phase in which one component exhibits positional order and a phase in which the other component exhibits positional order.…”
mentioning
confidence: 99%
See 1 more Smart Citation